Prevalence of HIV infection in parturient women and coverage of hiv testing during prenatal care and delivery in Brasília, Brazil - Tavares, Leonor Henriette de Lannoy Coimbra; Silva, Onã; Paz, Leidijany Costa; Lopes, Luiz Antonio Bueno; Oliveira, Maria Liz Cunha de (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Introduction: Prevalence of HIV seropositivity among pregnant women in Distrito Federal, Brazil, is unknown. Objective: To estimate the prevalence of HIV infection among parturient women and to describe the coverage of serology testing during prenatal care and delivery in the public health system of Distrito Federal, Brazil. Methods: Cross-sectional study, in which the variables sociodemographic data, information on prenatal care, and outcomes in HIV serology were collected from prenatal care cards and medical records of pregnant women residing in the Distrito Federal, whose deliveries occurred in public maternities between June 2009 and May 2010. The parturient was considered seropositive if a test was done with a confirmatory technique. Results: We studied 3,726 parturient women, of whom 3,627 (97.3%) had information about the outcome of HIV testing. Twelve ones were detected as HIV positive, representing a prevalence of 0.33% (95%CI: 0.19–0.58). The prevalence analysis by race/skin color, education level, and age range variables showed no statistically significant differences. The proportion of parturient women who presented the mother’s card was 94.6%. Coverage with two HIV tests in prenatal care was 22.1%. Conclusion: The prevalence of HIV seropositivity among pregnant women in public maternities in Distrito Federal is not significantly different from that estimated for Brazil. The coverage of testing for HIV was low.